Politics, ideology, and medical theory: interview with Christopher Hamlin - Christopher Hamlin; Rafael Mantovani (História, Ciências, Saúde: Manguinhos, 2022)
Abstract An interview with Christopher Hamlin in November 2020 in which he explains how he became interested in the history of public health. He talks about the outcomes of epidemics, the relationship between trust in science and moral imagination, why historians use previous public health experiences to think about the present, the role of discipline and ideology in problem-solving arrangements to deal with public health issues, and his new article on legal medicine.